From Refugees to Tourists: The Forfeit of Ukrainians’ Forced Migration Status in Bali - Hirshi Anadza; Suyeno; Khoiriyah Trianti; Mohamed Fajil Bin Abd Batau (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
The 2022 Russian invasion of Ukraine triggered an unexpected migration pattern, as some Ukrainians chose Bali, Indonesia, as their destination, challenging traditional distinctions between refugees and tourists. This study explores whether we should classify Ukrainians in Bali as refugees, given their tourist-like destination choices and behavior patterns. Through qualitative methodologies including content analysis, semi-structured interviews, observation, and migration theory analysis, the research reveals that Ukrainian presence in Bali aligns more closely with tourism than refugee characteristics, based on lifestyle-driven motivations, variable duration of stay, and destination choice preferences. The economic and social activities of Ukrainians in Bali resemble those of lifestyle migrants more than they do typical refugee patterns. The findings suggest that policy frameworks should maintain tourism-based approaches while acknowledging these migrants' complex circumstances and that traditional refugee-tourist classifications require revision to accommodate cases where conflict displacement intersects with lifestyle-based destination choices.